ANALISIS TINGKAT PENERAPAN SISTEM MANAJEMEN KESELAMATAN KONSTRUKSI (SMKK) PADA PROYEK KONSTRUKSI GEDUNG DI BANDAR LAMPUNG - Elian Zhafira; Galih Rio Prayogi; Hesty Wulandari (Nusantara Hasana Journal, 2025)
The construction industry has the highest rate of occupational accidents, including in Indonesia, accounting for 32% of all cases. Data from the Social Security Agency for Employment (BPJS Ketenagakerjaan) shows a significant increase in claims, from 234,370 cases in 2021 to 360,635 in 2023, with 25% of these accidents occurring in high-rise building projects. In 2023, the province of Lampung recorded 3,142 occupational accidents, ranking 19th nationally and 7th in Sumatra. This study employed a quantitative approach using structured questionnaires, followed by qualitative analysis to identify the key barriers in safety implementation. The level of implementation of the Construction Safety Management System (CSMS) in building projects across Bandar Lampung ranged from 74% to 95%, classified as good to satisfactory, with all projects fully allocating safety-related budgets. The primary obstacles identified include a weak safety culture among leaders and workers, regulations that are not well-aligned with field conditions, and a shortage of qualified safety supervisors. Strengthening safety education, updating regulatory frameworks, and increasing the number of competent safety professionals are critical measures to improve occupational safety in construction projects.